(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of the study is to study the professional skills of nurses in the surgical department. Materials and research methods. The study studied the quality of work of nurses (532 respondents) of the surgical departments of the Republican Scientific Center for Emergency Medical Care and its branches in Fergana, Syrdarya and Khorezm. To evaluate the activities of nurses, an expert assessment was carried out by heads of departments, doctors of departments and senior nurses with more than 10 years of experience, for a transparent, reliable and conscientious assessment of the quality and effectiveness of the work of nurses.Research results. No global health problem can be solved without raising the status, role, and potential of nurses in various health care institutions through systematic, coordinated efforts. In addition, the study and analysis of factors affecting working conditions, professional satisfaction, health, professional skills of nurses in the surgical department is important in improving the quality.